Acute Urinary Retention During Pregnancy—A Nationwide Population-Based Cohort Study in Taiwan. Issue 13 (March 2016) - Chen, Jeng-Sheng; Chen, Solomon Chih-Cheng; Lu, Chin-Li; Yang, Hsin-Yi; Wang, Panchalli; Huang, Li-Chung; Liu, Fu-Shun
Abstract : Abstract: The aim of the study was to investigate the epidemiology and risk factors of acute urinary retention (AUR) during pregnancy. We included all cases of pregnancies with AUR reported in Taiwan's Longitudinal Health Insurance Database from January 1, 1998, to December 31, 2011. Cases of AUR onset 1 day before delivery were excluded. The Cochrane-Armitage trend test and logistic regression analysis were used to evaluate the age distribution and types of deliveries of pregnant women. Chi-square tests and Fisher's exact test were performed to examine the association among all covariates. The odds ratios (OR) and 95% confidence intervals (CI) were estimated. We identified 308 cases of AUR in 65, 490 pregnancies. The risk of AUR during pregnancy was 0.47%. The peak incidence occurred between the 9th and 16th gestational weeks. Patients who experienced preterm delivery exhibited the highest risk for AUR (2.18%). Those with post-term delivery had the second highest risk (0.46%), and patients with a normal delivery exhibited the lowest risk (0.33%). Compared with normal delivery, preterm delivery carried a higher risk of AUR (OR: 6.33, 95% CI: 4.94–8.11). The AUR risk was higher for patients with advanced maternal age (>35 years old) than it was for those in the younger group (< 20 years old) (OR: 2.62, 95% CI: 1.18–5.81). Within the normal delivery group, higher incidences of urogenital infection, gestational diabetes mellitus, previous abortion, abnormal pelvis, disproportion, and endometriosis were noted in women with AUR than in those without AUR (all P values <0.05). Women with advanced maternal age and those who experienced preterm delivery had an increased risk for AUR. The peak incidence of AUR in normal pregnancies occurred between the 9th and 16th gestational weeks. Urogenital infection, gestational diabetes mellitus, previous abortion, abnormal pelvis, disproportion, and endometriosis were associated with AUR in women who underwent a normal delivery.